2020
DOI: 10.1096/fj.202001406r
|View full text |Cite
|
Sign up to set email alerts
|

Functional redundancy and compensation: Deletion of multiple murineCrispgenes reveals their essential role for male fertility

Abstract: Mammalian Cysteine-RIch Secretory Protein (CRISP) family includes four members present in sperm and reported to regulate Ca 2+ channels and fertilization. Based on our previous observations using single knockouts models and suggesting the existence of functional compensation among CRISP proteins, we investigated their relevance for male fertility by generating multiple Crisp gene mutants by CRISPR/ Cas9 technology. Whereas targeting of Crisp1 and Crisp3 yielded subfertile males with early embryo developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 70 publications
(201 reference statements)
4
36
1
Order By: Relevance
“…In agreement with this, a lower number of Crisp2 −/− sperm was observed within the cumulus mass during cumulus penetration assays, and hyperactivated motility was significantly lower in mutant sperm ( Brukman et al, 2016 ). Subsequent studies supported that these motility defects could be due to a stiffness of the midpiece in CRISP2 mutant sperm that impairs hyperactivation development and thus, egg coat penetration ( Lim et al, 2019 ; Curci et al, 2020 ). Different from Crisp1 −/− animals, sperm lacking CRISP2 exhibit a clear dysregulation of Ca 2+ homeostasis ( Brukman et al, 2016 ) that could explain the molecular mechanisms underlying the capacitation-associated defects in the mutant cells.…”
Section: Evidence On the Relevance Of Crisp Proteins For Fertilization And Fertility Through The Use Of Knockout Modelsmentioning
confidence: 98%
See 3 more Smart Citations
“…In agreement with this, a lower number of Crisp2 −/− sperm was observed within the cumulus mass during cumulus penetration assays, and hyperactivated motility was significantly lower in mutant sperm ( Brukman et al, 2016 ). Subsequent studies supported that these motility defects could be due to a stiffness of the midpiece in CRISP2 mutant sperm that impairs hyperactivation development and thus, egg coat penetration ( Lim et al, 2019 ; Curci et al, 2020 ). Different from Crisp1 −/− animals, sperm lacking CRISP2 exhibit a clear dysregulation of Ca 2+ homeostasis ( Brukman et al, 2016 ) that could explain the molecular mechanisms underlying the capacitation-associated defects in the mutant cells.…”
Section: Evidence On the Relevance Of Crisp Proteins For Fertilization And Fertility Through The Use Of Knockout Modelsmentioning
confidence: 98%
“…The fact that Crisp2 and Crisp4 are located in different chromosomes together with the availability of CRISP2 and CRISP4 single knockout colonies, led our laboratory to generate double Crisp2 −/− /Crisp4 −/− mice by natural mating ( Curci et al, 2020 ). Analysis of animal fertility revealed that, in spite of the participation of both proteins in key stages of the fertilization process, males lacking both proteins were fertile under normal laboratory conditions ( Curci et al, 2020 ).…”
Section: Evidence On the Relevance Of Crisp Proteins For Fertilization And Fertility Through The Use Of Knockout Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exactly how this is achieved is unknown although based on biochemical data it is presumed that a significant proportion of activity will be mediated via ion channel, including at least some of which remain to be characterized ( Gibbs et al, 2006 , 2011 ; Ernesto et al, 2015 ). Deletion of all four CRISPs in mice leads to severe subfertility ( Curci et al, 2020 ). For more information on the CRISPs and their roles in fertility and their evolutionary origins, readers are referred to ( Gaikwad et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%